Dynamics of births and juvenile recruitment in Mara-Serengeti ungulates in relation to climatic and land use changes - Ogutu, Joseph O.; Piepho, Hans-Peter; Dublin, H.T.; Bhola, N.; Reid, Robin S. (Wiley, 2011)
Natality and recruitment govern animal population dynamics, but their responses to fluctuating resources, competition, predation, shifting habitat conditions, density feedback and diseases are poorly understood. To understand the influences of climatic and land use changes on population dynamics, we monitored monthly changes in births and juvenile recruitment in seven ungulate species for 15 years (1989-2003) in the Masai Mara Reserve of Kenya. Recruitment rates declined for all species but giraffe, likely due to habitat alteration and increasing vulnerability of animals associated with recurrent severe droughts, rising temperatures, unprecedentedly strong and prolonged El Niño-Southern Oscillation (ENSO) episodes, expansion of settlements, cultivation and human population growth in pastoral ranches adjoining the reserve. Birth rate showed strong and humped relationships with moving averages of monthly rainfall, whereas recruitment responded strongly to cumulative past rainfall. Increasing livestock incursions into the reserve depressed recruitment rate for quarter-grown topi. Expansion of pastoral settlements depressed birth rate in impala, zebra and giraffe. Frequent ENSO-related droughts caused progressive habitat desiccation and hence nutritional shortfalls for ungulates. The responses to climatic, land use and resource influences did not reflect body size, migratory or resident lifestyle, dietary guild, digestive physiology or degree of synchrony of breeding of the ungulate species.